The Currency Union Effect: A PPML Re-assessment with High-Dimensional Fixed Effects - Mario Larch; Joschka Wanner; Yoto V. Yotov; Thomas Zylkin (Center for Economic Studies and ifo Institute (CESifo), 2017)
Recent work on the effects of currency unions (CUs) on trade stresses the importance of using many countries and years in order to obtain reliable estimates. However, for large samples, computational issues limit choice of estimator, leaving an important methodological gap. To address this gap, we unveil an iterative PPML estimator which flexibly accounts for multilateral resistance, pair-specific heterogeneity, and correlated errors across countries and time. When applied to a comprehensive sample with more than 200 countries trading over 65 years, these innovations flip the conclusions of an otherwise rigorously-specified linear model. Our estimates for both the overall CU effect and the Euro effect specifically are economically small and statistically insignificant. The effect of non-Euro CUs, however, is large and significant. Notably, linear and PPML estimates of the Euro effect increasingly diverge as the sample size grows.
Keywords: C13; C21; F10; F15; F33; 330; currency unions; PPML; high-dimensional fixed effects